IEM teaching and research at the crossroads of innovation, digitalisation and sustainability: Proceedings of the 14th EPIEM Conference 2021 - Bernd M. Zunk; Amila Omazic (Technische Universität Graz, Institut für Betriebswirtschaftslehre und Betriebssoziologie, 2021)
[Preface:] For the EPIEM (European Professors of Industrial Engineering and Management) network - and its goal to initiate and foster collaboration between IEM academics across Europe - annual confer-ences are of vital importance. Thus, it is a great honour and pleasure for me as the current Presi-dent of EPIEM, to present the proceedings of the 14th EPIEM Conference 2021 hosted by Graz University of Technology. Considering the background of the ongoing Covid-19 pandemic, this EPIEM conference had to be organized in a virtual environment. And I am all the more pleased that you - the members of the IEM community and the contributors to this EPIEM conference proceedings - took this opportunity to attend this conference, to submit a research paper in order to present it and to discuss the impli-cations of your research with the conference participants. This kind of exchanging knowledge and sharing experiences is very important for us as a scientific community as EPIEM conferences should open the doors between motivated professors, lecturers, scientists and mindful thinkers in the field of IEM. Therefore, it is an honour for me to invite you al-ready now to the upcoming 15th EPIEM Conference 2022 at Graz University of Technology (note: details you may find online at www.epiem.org) and to participate actively in our constantly growing EPIEM network. (...)
Keywords: 650